FRI0379 VARIATIONS IN THE UTILIZATION OF BILATERAL TOTAL KNEE ARTHROPLASTY IN THE MANAGEMENT OF OSTEOARTHRITIS. (2nd June 2020) - Mehta, B.; Ho, K.; Bido, J.; Parks, M.; Russell, L.; Goodman, S.; Ibrahim, S.
Abstract : Background: A third of knee osteoarthritis presents with bilateral symptomatic arthritis. In these patients, treatment options include either a staged Unilateral Total knee arthroplasty (UTKA) procedure, or a simultaneous Bilateral TKA (BTKA) procedure. Even though literature regarding outcomes in BTKA procedure has not consistently been favorable, it remains popular in select patients due to use of a single anesthetic, shorter overall surgical time, lower cost and lower overall use of narcotics. African Americans (AAs) have lower utilization and worse outcomes in UTKA literature. It is unclear whether these racial variations extend to BTKA. Objectives: We sought to examine BTKA vs UTKA utilization rates and outcomes comparing AA and White patients. Methods: National Inpatient Sample (NIS) - Healthcare Cost and Utilization Project (HCUP) database (2007-2016) was used. We identified all patients ≥ 50 years who underwent elective primary TKA using ICD-9-CM code 81.54 for UTKA and BTKA from January 1, 2012 to September 30, 2015, and ICD-10-CM codes 0SRC0x and 0SRD0x thereafter. Patients with inflammatory arthritis, pathologic fractures, metastatic disease and avascular necrosis were excluded. Major in-hospital complications included post-operative myocardial infarction, prosthetic device complication, surgical wound infection, and venous thromboembolism. Differences in temporal trends in utilization and major in-hospital complications of BTKA vs UTKA were compared between AAs and Whites. Multivariable logistic regression models were used to assess differences in both these trends between AAs and Whites after adjusting for individual (age, sex, Elixhauser comorbidity index, and morbid obesity), hospital level (hospital volume, bed size, region and teaching status) and community level (median household income) variables. Discharge weights were used to enable nationwide estimates. Multiple imputation was performed for missing race variable (11.9%). Results: From 2007 to 2016, an estimated 276, 194 BTKA (unweighted observations 56, 675) and 5, 528, 429 UTKA (unweighted observations 1, 131, 329) were identified (Table 1). Females had a higher proportion of TKAs performed (62.1% UTKA vs 55.9% BTKA). Patients had fewer comorbidities (measured by the Elixhauser Index) when undergoing BTKA compared to UTKA. The proportion of BTKA amongst all TKAs declined from 5.53% in 2007-08 to 4.03% in 2015-16. AAs continued to have significantly lower proportion of BTKA utilization compared to Whites (4.68% in AAs vs 6.08% in Whites in 2007-08, whereas 3.28% in AAs vs 4.19% in Whites in 2015-16, adjusted p < 0.001) (Figure 1a ). In-hospital complication rates for UTKA and BTKA were significantly higher in Whites compared to AAs throughout the study period (0.77% in AAs vs 0.9% in Whites in 2007-08, whereas 0.69% in AAs vs 0.83% in Whites in 2015-16, adjusted p < 0.001) (Figure 1b ). The results were similar after imputation of missing race values. Conclusion: In this nationwide sample of patients from 2007 to 2016, we found that AAs have lower utilization rate of BKTA compared to Whites, however the in-hospital complication rates were significantly higher in Whites. References: N/A Disclosure of Interests: Bella Mehta: None declared, Kaylee Ho: None declared, Jennifer Bido: None declared, Michael Parks Consultant of: Zimmer Biomet, Linda Russell: None declared, Susan Goodman Shareholder of: Reginosine- Investment, Grant/research support from: Novartis, Horizon, Consultant of: Novartis, Celgene, UCB, Said Ibrahim: None declared